2003
DOI: 10.1242/dev.00493
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal patterning genes are active during embryogenesis in Arabidopsis

Abstract: Epidermal cells in the root of Arabidopsis seedling differentiate either as hair or non-hair cells, while in the hypocotyl they become either stomatal or elongated cells. WEREWOLF (WER) and GLABRA2 (GL2) are positive regulators of non-hair and elongated cell development. CAPRICE (CPC) is a positive regulator of hair cell development in the root. We show that WER, GL2and CPC are expressed and active during the stages of embryogenesis when the pattern of cells in the epidermis of the root-hypocotyl axis forms. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Our data show that proper GL2 expression in the embryo requires JKD action. GL2 expression in the embryo depends on WER and CPC (Costa and Dolan, 2003), but not on the action of the receptor kinase SCM because no changes in GL2 expression were found in either scm embryos or in triple mutants of scm with srf1 and srf2, encoding the two members most closely related to SCM (Kwak and Schiefelbein, 2006). Therefore, the embryonic function of JKD must be independent from SCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show that proper GL2 expression in the embryo requires JKD action. GL2 expression in the embryo depends on WER and CPC (Costa and Dolan, 2003), but not on the action of the receptor kinase SCM because no changes in GL2 expression were found in either scm embryos or in triple mutants of scm with srf1 and srf2, encoding the two members most closely related to SCM (Kwak and Schiefelbein, 2006). Therefore, the embryonic function of JKD must be independent from SCM.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, SCM negatively regulates WER in T cells, which enables these cells to adopt the H cell fate, whereas in the A cells, WER abundance becomes relatively high, resulting in activation of the non-hair fate differentiation pathway. However, the epidermal cell pattern is set up during embryogenesis (Costa and Dolan, 2003), where SCM action is not required. This suggests that other factors perceive the initial signals that pattern root epidermal cell types.…”
Section: Introductionmentioning
confidence: 99%
“…The position-dependent patterning of root epidermal gene expression is known to be established during early stages of embryogenesis (Costa and Dolan, 2003;Lin and Schiefelbein, 2001). To explore further the unexpected expression pattern of GL3 and EGL3, we examined the GL3::GUS and EGL3::GUS activity during embryogenesis.…”
Section: Gl3 and Egl3 Function In The Embryonic Root And During Hypocmentioning
confidence: 99%
“…Previous studies have shown that the position-dependent cellular pattern of root epidermal cells is determined by interactions of six patterning genes: CPC, ETC, GL2, GL3͞EGL3, TTG, and WER (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). CPC, GL2, and WER are preferentially expressed in N position cells upon seed germination (6,(9)(10)(11)(12), and regulate the preferential expression of GL3͞EGL2 at H position cells (15). Therefore, their appropriate expression is essential for accurate regulation of root epidermal patterning.…”
mentioning
confidence: 99%